Freedom and possession in the letters of Andrzej Bobkowski - Ruszar, Józef Maria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
For Bobkowski, to maintain personal freedom based on material independence achieved through his own work was a fundamental existential issue. Freedom and financial independence were: a declaration, a life’s motto and an economic programme. The writer’s concept was, eventually, reduced to a change of his status as a political exile to the situation of an economic migrant who also supported Poland’s freedom.